Skrining Tekanan Darah sebagai Upaya Deteksi Dini Hipertensi pada Masyarakat Usia Produktif di Kelurahan Menur Pumpungan - Wiwid Samsulhadi; Yustisia Amalia; Cityta Putri Kwarta; Lentera Afrida Kusumawardani; Sasi Widuri; Putu Ayu Dhana Reswari (Health Care : Journal of Community Service, 2025)
Hypertension is one of the primary health issues among the productive-age group, often remaining undetected due to low public awareness regarding routine screenings. This community service project aims to conduct blood pressure screenings while simultaneously increasing awareness of hypertension risks among the productive-age population in Menur Pumpungan Village. The activity was conducted offline through blood pressure measurements using standardized digital tensimeters, accompanied by brief education on hypertension and its prevention. The participants consisted of 100 individuals from the general public, including both productive-age men and women. The results indicated that a portion of the participants fell into the prehypertension and hypertension categories, while others maintained normal blood pressure levels. These findings suggest a significant potential for hypertension issues within the productive-age population. This initiative underscores the importance of routine blood pressure checks for early detection and strengthens the role of community service in supporting promotive and preventive health efforts at the village level.